Nitrite Therapy Ameliorates Myocardial Dysfunction via H(2)S and Nuclear Factor‐Erythroid 2‐Related Factor 2 (Nrf2)‐Dependent Signaling in Chronic Heart Failure - Donnarumma, Erminia (J Am Heart Assoc, 2016)
BACKGROUND: Bioavailability of nitric oxide (NO) and hydrogen sulfide (H(2)S) is reduced in heart failure (HF). Recent studies suggest cross‐talk between NO and H(2)S signaling. We previously reported that sodium nitrite (NaNO (2)) ameliorates myocardial ischemia‐reperfusion injury and HF. Nuclear factor‐erythroid‐2‐related factor 2 (Nrf2) regulates the antioxidant proteins expression and is upregulated by H(2)S. We examined the NaNO (2) effects on endogenous H(2)S bioavailability and Nrf2 activation in mice subjected to ischemia‐induced chronic heart failure (CHF). METHODS AND RESULTS: Mice underwent 60 minutes of left coronary artery occlusion and 4 weeks of reperfusion. NaNO (2) (165 μg/kgic) or vehicle was administered at reperfusion and then in drinking water (100 mg/L) for 4 weeks. Left ventricular (LV), ejection fraction (EF), LV end diastolic (LVEDD) and systolic dimensions (LVESD) were determined at baseline and at 4 weeks of reperfusion. Myocardial tissue was analyzed for oxidative stress and respective gene/protein‐related assays. We found that NaNO (2) therapy preserved LVEF, LVEDD and LVSD at 4 weeks during ischemia‐induced HF. Myocardial malondialdehyde and protein carbonyl content were significantly reduced in NaNO (2)‐treated mice as compared to vehicle, suggesting a reduction in oxidative stress. NaNO (2) therapy markedly increased expression of Cu,Zn‐superoxide dismutase, catalase, and glutathione peroxidase during 4 weeks of reperfusion. Furthermore, NaNO (2) upregulated the activity of Nrf2, as well as H(2)S‐producing enzymes, and ultimately increased H(2)S bioavailability in ischemia‐induced CHF in mice as compared with vehicle. CONCLUSIONS: Our results demonstrate that NaNO (2) therapy significantly improves LV function via increasing H(2)S bioavailability, Nrf2 activation, and antioxidant defenses.